The crystal structure of (2E,2′E)-,2,2′-bis[1-(2-pyrazinyl)ethylidene]carbonimidic dihydrazide, C13H15N9 - Ji Xiao-Hui; Liu Ye; Liu Mei-Ling; Zhao Juan; Lu Jiu-Fu (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C13H15N9, monoclinic, C2/c (no. 15), a = 22.827(5) Å, b = 7.8830(16) Å, c = 16.020(3) Å, β = 98.95(3)°, V = 2847.6(10) Å3, Z = 8, Rgt(F) = 0.0416, wRref(F2) = 0.1331, T = 293(2) K.